Suhu,Kelembaban Dan Pencahayaan Sebagai Faktor Risiko Kejadian Penyakit ISPA Pada Balita di Kecamatan Balaesang Kabupaten Donggala - Dedi Mahyudin Syam; Ronny Ronny (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
In the case of respiratory diseases Balaesang District of Donggala in the last three years are likely to experience fluctuations in 2012 with the number of 1166, 2013 and 2014 the number of patients 874 patients number 1,037. These data represent the number of patients with respiratory disease in general. According to data obtained from the observation that the data ISPA patients at the age of five from January to March 2015 the number of people 50 toddlers.This study aims to assess the physical condition of the house and the sources of pollution in the home with a disease incidence of ISPA Toddlers in Sub Balaesang Donggala 2015.The method used is observational analytic design case control study in April and May 2015. The sample was selected by purposive sampling with a sample size of 100 Toddler covering 50 cases and 50 controls. Data were analyzed by using a system of tabulation and statistical tests SPSS version 19.0 with Odds Ratio test and logistic regression methods Backward LR.The results showed that the variable temperature with a p-value (0.00) of <0.05, OR value = 0173 (0072-0417), the humidity with a p-value (0.00) of <0.05, OR = 0.145 (0060-0353) and lighting with a p-value (0.00) of <0.05, OR = 0181 (0076-0428).Concluded that based on the results obtained, the variable temperature, humidity, and the lighting is a risk factor is significant on the incidence of respiratory disease in infants In Sub Balaesang Donggala. Keyword : Risk factor, ISPA, Infant